Detailed field test of yaw-based wake steering. Issue 5 (September 2016) - Fleming, P; Churchfield, M; Scholbrock, A; Clifton, A; Schreck, S; Johnson, K; Wright, A; Gebraad, P; Annoni, J; Naughton, B; Berg, J; Herges, T; et al.
Abstract: This paper describes a detailed field-test campaign to investigate yaw-based wake steering. In yaw-based wake steering, an upstream turbine intentionally misaligns its yaw with respect to the inflow to deflect its wake away from a downstream turbine, with the goal of increasing total power production. In the first phase, a nacelle-mounted scanning lidar was used to verify wake deflection of a misaligned turbine and calibrate wake deflection models. In the second phase, these models were used within a yaw controller to achieve a desired wake deflection. This paper details the experimental design and setup. All data collected as part of this field experiment will be archived and made available to the public via the U.S. Department of Energy's Atmosphere to Electrons Data Archive and Portal.